Pintar dan Kreatif Memanfaatkan Teknologi Digital untuk Pengembangan Desa Wisata - Dian Harmaningsih; Susi Yunarti; Siti Komsiah; Wijayanti Wijayanti (Universitas Persada Indonesia YAI, 2023)
In order to help government programs to continue to activate national tourism, one ofthem is by developing tourist villages. Because there is still a lot of potential in many areasthat have not been explored and need to be developed into attractive tourist objects. So thatlocal people know and understand what to do, to make their village potential as a nationaltourism object, we can help them to do comparative studies digitally through browsing andsearching about various things related to tourism potential in various places, both domesticand global.Community service activities have been carried out on Youth Insight Development andTraining, Karang Taruna Dukuh Barak II Margoluwih Seyegan – Sleman, Yogyakarta. Thisactivity is a form of participating in the tourism village development program by providingtraining to use digital technology to add insight and dig up a lot of information about tourismboth domestically and globally, so that community members know what can still be done todevelop the potential of their village as an attractive tourist attraction.